Design of an oxygen concentrator according to ISO 80601-2-69 standards - Vigil Wuilber Mamani-Cori; Nilton Juan Zeballos-Hurtado; Arturo Jesús Cosi-Blancas (Dyna)
This work focuses on the design, construction and economic analysis of an oxygen concentrator in the city of Moquegua, Peru, under ISO 80601-2-69 standards. The methodology used was experimental, consisting of the design and construction of an oxygen concentrator, as well as its economic analysis. The results of the prototype tests indicate that it provides oxygen with a concentration of 95%, up to 10 litres/min, consuming 280 W of power, being powered by 220 V alternating current, working under a process called oscillating pressure absorption. The final cost of the device was S/1220.80, which contrasts with the cost of similar equipment that in the market have a value of S/1500.00 and that in pandemic 2020 reached S/15000.00. In conclusion, the manufacture of an oxygen concentrator in Moquegua is both technically and economically feasible.